Dampak Perundungan (Bullying) Verbal terhadap Empati Korban pada Siswa SMPN 7 Muaro Jambi - Ledita Ezy Maulany; Rasimin Rasimin; Affan Yusra (Universitas Batanghari Jambi, 2022)
This study aims to measure the frequency of verbal bullying and victim empathy, as well as to determine the impact of verbal bullying on victim empathy at SMPN 7 Muaro Jambi. This type of research is quantitative research with ex-post facto methodology. This research was conducted on students of SMPN 7 Muaro Jambi grade VIII a, b, c, and d. Data was taken on October 22, 2021 and obtained by giving a questionnaire or questionnaire to 54 students. The results showed that the percentage for verbal bullying was 58.87% with an occasional frequency. While the percentage for the empathy variable is 62.04% with frequent frequency. The significant value is 0.001 < 0.05 and the t count is 6.277 > 1.674. So it can be concluded that the impact of verbal bullying on victim emphathy has a positive directive.